Robustheitsanalyse stark fehlersicherer Schaltungen mit SAT-basierter Testmustererzeugung - Hunger, Marc; Hellebrand, Sybille; Czutro, Alexander; Polian, Ilia; Becker, Bernd (3. GMM/GI/ITG-Fachtagung "Zuverlässigkeit und Entwurf")

Jenseits der Lesbarkeit. Unsichtbare Spuren und Spuren der Unsichtbarkeit in der Erzählpoetik Patrick Roths - van Laak, Lothar (Patrick Roth. Erzählen zwischen Hölderlin und Hollywood)

Literarische Anthropologie - van Laak, Lothar (Methodengeschichte der Germanistik)

„... im großen Sensorium der Schöpfung Gottes...“ – Johanneische Liebestheologie als spinozistische Poeto-Philosophie bei Johann Gottfried Herder - van Laak, Lothar (Sprache und Literatur 40)

Medien und Medialität des Epischen in Literatur und Film des 20. Jahrhunderts: Bertolt Brecht – Uwe Johnson – Lars von Trier - van Laak, Lothar

Lehrerkooperation an Gymnasien - Eine explorative Untersuchung zu Ausprägung und Wirkungen am Beispiel des naturwissenschaftlichen Unterrichts. Dissertation an der Universität Duisburg-Essen - Kullmann, Harry

Skalen zur Erfassung der unterrichtsbezogenen Lehrerkooperation - Kullmann, Harry ({Instrumente fachdidaktischer Unterrichtsforschung})

Christa Wolf, Der geteilte Himmel - Elit, Stefan (Kindlers Literaturlexikon, 3., völlig neubearb. Aufl., Bd. 17: Vil-Z)

Abgrenzung und Synthese. Lateinische Dichtung und volkssprachliche Traditionen in Renaissance und Barock, hg. v. Marc Föcking u. Gernot Michael Müller, Heidelberg 2007 (Romanisch-Germanische Monatsschrift; Beihefte 31) - Elit, Stefan (NlatJb 11 (unter dem Titel: Lateinische und vernakulare Literaturen im Kontakt: Fallstudien frühneuzeitlicher Modellationen))

Kleist-Handbuch. Leben – Werk – Wirkung, hg. v. Ingo Breuer, Stuttgart/Weimar 2009 - Elit, Stefan (JbIG 41, H. 2 (Jahrbuch für brandenburgische Landesgeschichte))

„Die höfischen Künste in ‚Flore und Blanscheflur‘ und ‚Apollonius von Tyrland‘“ - Egidi, Margreth (Interartifizialität. Die Diskussion der Künste in der mittelalterlichen Literatur (Sonderh. der ZfdPh 128))

„Verborgene Heiligkeit. Legendarisches Erzählen in der Alexiuslegende“ - Egidi, Margreth (Literarische und religiöse Kommunikation in Mittelalter und Früher Neuzeit [DFG-Symposion 2006])

Jean Piaget, Die Entwicklung der physikalischen Mengenbegriffe beim Kinde: Erhaltung und Atomismus - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Jean Piaget, Das Erwachen der Intelligenz beim Kinde - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Early Top-Down Influences in Control of Attention: Evidence from the Attentional Blink - Hilkenmeier, Frederic; Tünnermann, Jan; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
The relevance of top-down information in the deployment of attention has more and more been emphasized in cognitive psychology. We present recent findings about the dynamic of these processes and also demonstrate that task relevance can be adjusted rapidly by incoming bottom-up information. This adjustment substantially increases performance in a subsequent task. Implications for artificial visual models are discussed.
Keywords: visuo-spatial attention; top-down control; task relevance; artificial visual attention; attentional blink

Attention Speeds Up Visual Information Processing: Selection for Perception or Selection for Action? - Weiß, Katharina; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
Attention speeds up information processing. Although this finding has a long history in experimental psychology, it has found less regard in computational models of visual attention. In psychological research, two frameworks explain the function of attention.Selection for perception emphasizes that perception- or consciousness-related processing presupposes selection of relevant information, whereas selection for action emphasizes that action constraints make selection necessary. In the present study, we ask whether or how far attention, as measured by the speed-up of information processing, is based on selection for perception or selection for action. The accelerating effect was primarily based on selection for perception, but there was also a substantial effect of selection for action.
Keywords: visuo-spatial attention; prior entry; selection for action; selection for perception

What you see is what you set – the position of moving objects - Priess, Heinz-Werner; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
Human observers consequently misjudge the position of moving objects towards the direction of motion. This so called flash-lag effect is supposed to be related to very basic processes such as processing latencies in the human brain. In our study we show that this effect can be inversed by changing the task-set of the observer. A top-down change of the observers attentional set leads to a different perception of otherwise identical scenes. Cognitive theories regard the misperception of the moving object as an important feature of attention-mediated processing, because it reflects the prioritized processing of important objects.

China's provincial disparities and the determinants of provincial inequality - Gries, Thomas; Redlin, Margarete (Journal of Chinese Economic and Business Studies)

My Mother: My Best Friend? Adults’ Relationships with Significant Others Across the Lifespan - Buhl, Heike M. (Journal of Adult Development)
In order to investigate the significance of adults’ relationship to their parents, this relationship is compared to relationships with siblings, friends, partners, and children. German adults (N = 902) between the ages of 20 and 86 completed the Network of Relationships Inventory (Furman and Buhrmester 1992). Participants felt most supported by their partners, followed by their children, mothers, friends, fathers, and siblings. Conflicts were more frequently found within the family (especially with the partner, followed by children, mothers, fathers, and siblings) than with friends. Except for partner relationships, both conflict and support decreased with age. Concerning relative power within their relationships, partners, mothers, and siblings are seen as equals, friends and especially fathers are perceived as more powerful, and children as less, yet increasingly powerful. Regarding all relationship types and relationship qualities, the differences between women and men were small.
Keywords: Family; Friends; Support; Conflict; Power

Zusammenhänge zwischen der Fähigkeit zur Perspektivenübernahme und dem Textverstehen im Vor- und Grundschulalter - Buhl, Heike M.; Möller, Franziska; Oebser, Manuela; Stein, Freia; Noack, Peter (Diskurs Kindheits- und Jugendforschung)
Im vorliegenden Beitrag wird der Zusammenhang zwischen der Fähigkeit zur Perspektivenübernahme und sinnverstehendem Lesen dargestellt. Auf der Grundlage von Arbeiten zum Textverstehen sowie zu Perspektivenübernahme und Theory of Mind wurde ein positiver Zusammenhang zwischen Perspektivenübernahmefähigkeit und Textverstehensleistung erwartet. Diese Hypothese wurde an zwei Stichproben unterschiedlichen Alters geprüft: In der ersten Studie beantworteten 37 Vorschulkinder Fragen zu vorgelesenen Geschichten sowie Perspektivenübernahme-Aufgaben. Zwischen den Bereichen fand sich eine deutliche positive Korrelation, die bei Kontrolle der Intelligenz erhalten blieb. An der zweiten Studie nahmen 69 Grundschulkinder der dritten Jahrgangsstufe teil, die Texte lasen und Aufgaben dazu wie auch zur Perspektivenübernahme bearbeiteten. In dieser Stichprobe fand sich der erwartete Zusammenhang ausschließlich in der Teilgruppe der guten Leser. Er blieb bei Kontrolle der Intelligenz erhalten. Die Ergebnisse werden auch in Hinblick auf die Förderung der Lesekompetenz diskutiert.
Keywords: Textverstehen; Lesekompetenz; Perspektivenübernahme; Theory of Mind; Kindesalter

Wilhelm Worringer: Abstraktion und Einfühlung - Öhlschläger, Claudia (Kindlers Literatur Lexikon. Dritte, völlig neu bearbeitete Auflage. 18 Bände inkl. einem Registerband)

Soziale und ästhetische Praxis der höfischen Fest-Kultur im 16. und 17. Jahrhundert

"Wortschatzsammler" im Unterricht: Entwicklung und Evaluation eines strategieorientierten, unterrichtsintegrierten Förderkonzepts - Motsch, H.J; Brüll, T (Vierteljahresschrift für Heilpädagogik und ihre Nachbargebiete)

Liebes-Geschichten: Von Petrarcas Amorallegorien zu Fontenelles Allegorisierungen der Liebe - Steigerwald, Jörn (Comparatio. Zeitschrift für Vergleichende Literaturwissenschaft 1 / 1)

Narration und Ethik. Bd. 1 der Reihe „Ethik-Text-Kultur“

Faszination des Ornamentalen: Zur Tiefe der Oberflächenästhetik in Fotografien Andreas Gurskys - Öhlschläger, Claudia (Faszination. Historische Konjunkturen und heuristische Tragweite eines Begriffs)

Die Distanz bewohnen ́. Zur Ethik der Scham bei Adalbert Stifter - Öhlschläger, Claudia (Jahrbuch der Deutschen Schillergesellschaft LI II/2009)

Lemma Christian Thomasius: Von der Nachahmung der Franzosen - Steigerwald, Jörn (Poetiken. Autoren – Texte – Begriffe)

Lemma D.A.F. de Sade: Idée sur les romans - Steigerwald, Jörn (Poetiken. Autoren – Texte – Begriffe)

Verräumlichte Augen-Blicke. Narrative Visualisierungsstrategien in Mme de Staëls „Corinne“ und Goethes „Wahlverwandtschaften“ - Steigerwald, Jörn (Lesbarkeit der Romantik)

Sujets de l’amour. Formes de la représentation de soi dans la société du cours d’après „Le Favori“ - Steigerwald, Jörn (Mme de Villedieu et le théâtre. Actes du colloque de Lyon (11 et 12 septembre 2008))

Von der (Un-)Möglichkeit sozialer Praxis im Theaterstaat von Louis XIV: Madeleine de Scudérys dialogische Inszenierung von Festbeschreibungen - Steigerwald, Jörn (Soziale und ästhetische Praxis der höfischen Fest-Kultur im 16. und 17. Jahrhundert)

Galanterie als Kristallisations- und Kreuzungspunkt um 1700: Eine Problemskizze - Steigerwald, Jörn (Kleine Schriften des IZEA 1, 2009. Galanterie und Frühaufklärung)

Soziale und ästhetische Praxis der höfischen Fest-Kultur: Eine Problemskizze - Steigerwald, Jörn (Soziale und ästhetische Praxis der höfischen Fest-Kultur im 16. und 17. Jahrhundert)

Les arts et l’amour galant: à propos de „La Promenade de Versailles“ de Madeleine de Scudéry - Steigerwald, Jörn (Littératures classiques 2009 / 3, Les Discours artistiques de l'amour à l'âge clas- sique. Sous la direction de Kirsten Dickhaut / Alain Viala)

Konzessive Konstruktionen. Ein Verfahren zur Rekonstruktion von Konzessionen - Rezat, Sara (Zeitschrift für Germanistische Linguistik 37)

Feasibility of free space quantum key distribution with coherent polarization states - Elser, D.; Bartley, Tim; Heim, B.; Wittmann, Ch; Sych, D.; Leuchs, G. (New Journal of Physics)
We demonstrate for the first time the feasibility of free space quantum key distribution with continuous variables under real atmospheric conditions. More specifically, we transmit coherent polarization states over a 100 m free space channel on the roof of our institute's building. In our scheme, signal and local oscillator (LO) are combined in a single spatial mode, which auto-compensates atmospheric fluctuations and results in an excellent interference. Furthermore, the LO acts as a spatial and spectral filter, thus allowing unrestrained daylight operation.

Sprache und Interaktion im Kindergarten. Eine quantitativ-qualitative Analyse der sprachlichen und kommunikativen Kompetenzen von drei- bis sechsjährigen Kindern - Albers, Timm

Wenn Wörter auf Wanderschaft gehen .... Aspekte kultureller, nationaler und geschlechtsspezifischer Differenzen in deutschsprachiger Migrationsliteratur - Zierau, Cornelia

„Ohne Deutsch kann man hier nichts machen“ – Förderung von Schüler(-innen) mit Migrationshintergrund - Zierau, Cornelia (Deutschmagazin 2/2009)

Accurate RTOS Modelling and Analysis with SystemC - Zabel, Henning; Müller, Wolfgang; Gerstlauer, Andreas (Hardware Dependent Software - Principles and Practice)
Today, mobile and embedded real-time systems have to cope with the migration and allocation of multiple software tasks running on top of a real-time operating system (RTOS) residing on one or several system processors. Each RTOS has to be configured towards the individual needs of the application and environment. For this, different scheduling strategies and task priorities have to be evaluated in order to keep execution and response times for a given task set. Abstract RTOS simulation is applied to analyze different parameters in early design phases. This chapter presents a SystemC RTOS library for abstract yet accurate RTOS sim- ulation, supporting modeling of preemption in the presence of prioritized and nested interrupts. After introducing basic principles of abstract RTOS simula- tion, we present our SystemC library in detail. Thereafter, we discuss related approaches and close with applications in electronic automotive systems design and some evaluations.
Keywords: RTOS Modelling; RTOS Simulation; SystemC; Task Scheduling; Interrupt Analysis

Hardware-dependent Software - Introduction and Overview - Ecker, Wolfgang; Müller, Wolfgang; Dömer, Rainer (Hardware Dependent Software - Principles and Practice)
Rapidly rising system complexity has created a growing productivity gap in the design of electronic systems. One critical component is Hardware-dependent Software (HdS), the importance of which is often underestimated. In this chap- ter, we introduce HdS and illustrate its role in the overall system design context. We also provide a brief overview and define a basic HdS terminology and con- clude with a brief outlook over the following chapters in this book.
Keywords: Hardware-dependent Software; Systems Complexity; Productivity Gap

Jana Hrdličková: Es sieht schlimm aus in der Welt. Der moralische Appell in den Hörspielen von Marie Luise Kaschnitz - Famula, Marta (Brünner Beiträge zur Germanistik und Nordistik, 14 (2009) H. 1–2)

Gleichnisse des erkenntnistheoretischen Scheiterns. Thomas Glavinics Roman Die Arbeit der Nacht in der Tradition des labyrinthischen Erzählens bei Franz Kafka und Friedrich Dürrenmatt - Famula, Marta (Transitträume. Beiträge zur deutschsprachigen Gegenwartsliteratur (Germanistik und Gegenwartsliteratur 4))

Ermittlung der Verluste von Schneckengetrieben mit ZK-Schnecke - Magyar, Balázs; Horák, P (GÉP)

Übergang Förderschule-Beruf: Neue Wege der Gestaltung - Heger, M-; Laubenstein, Désirée (In: Impulse Nr. 4)

Sprachwandel

Das Niederdeutsche in der Sprachgeschichtsschreibung - Tophinke, Doris (Korrespondenzblatt des Vereins für Niederdeutsche Sprachforschung)

Vom Vorlesetext zum Lesetext: Zur Syntax mittelniederdeutscher Rechtsverordnungen im Spätmittelalter - Tophinke, Doris (Oberfläche und Performanz. Untersuchungen zur Sprache als dynamische Gestalt)

Wirklichkeitserzählungen im Internet - Tophinke, Doris (Wirklichkeitserzählungen. Felder, Formen und Funktionen des nicht-literarischen Erzählens)

Sprachwandel (Basisartikel) - Tophinke, Doris (Praxis Deutsch)

Consolidation in banking and financial stability in Europe: Empirical evidence - Uhde, André; Heimeshoff, Ulrich (Journal of Banking & Finance)
Using aggregate balance sheet data from banks across the EU-25 over the period from 1997 to 2005 we provide empirical evidence that national banking market concentration has a negative impact on European banks’ financial soundness as measured by the Z-score technique while controlling for macroeconomic, bank-specific, regulatory, and institutional factors. Furthermore, our analysis reveals that Eastern European banking markets exhibiting a lower level of competitive pressure, fewer diversification opportunities and a higher fraction of government-owned banks are more prone to financial fragility whereas capital regulations have supported financial stability across the entire European Union.
Keywords: Market structure; Financial stability; Banking regulation

Darstellung, Anordnung und implizite Schlussfolgerung. Über das Verhältnis von Dichtung und Moral aus philosophischer Perspektive. Eine platonische Kritik der Postmoderne - Hagengruber, Ruth Edith (Narration und Ethik)

60 Jahre BRD – 60 Jahre DAB: Frauen schreiben Geschichte anders! Hannah Arendt gegen Theodor W. Adorno - Hagengruber, Ruth Edith (Konsens)

Interview mit Martha Nussbaum - Hagengruber, Ruth Edith (Konsens 1+2 (2009))
Keywords: Interview; Martha Nussbaum

Kölving, Ulla; Courcelle, Olivier. Émilie du Châtelet. Éclairages et documents nouveaux (Ferney-Voltaire: Centre International d'Étude du XVIIIe Siècle, 2008) - Hagengruber, Ruth Edith (Francia-Recensio. Frühe Neuzeit – Revolution – Empire (1500–1815).)

Die Metaphysik des Erhalts. Politik und Ökonomie in der Città del Sole des Tommaso Campanella - Hagengruber, Ruth Edith (Reneszansz filozofia/ Renaissance in Hungary)

Theory of Action in Cooperative Systems - Hagengruber, Ruth Edith (HNI Jahresbericht / HNI Annual Report)

History and philosophical foundations of AI - Hagengruber, Ruth Edith (HNI Heinz Nixdorf Institut Nachrichten)

Soziale Platzierung: Weder Geld noch Bildung allein entscheiden - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Quellmalz, Kirsten (Haushalt & Bildung)

Geld – zentraler Schlüssel für gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Haushalt & Bildung)

Ressourcen – Vielfalt, Zusammenwirken und Lebensqualität - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Haushalt & Bildung)

Ressourcen – Voraussetzung für Teilhabe- und Gestaltungsmöglichkeiten - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Ressourcen im Rahmen des Haushaltshandelns - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Haushalt & Bildung)

Die Vorwürfe gegen Heinrich IV. - eine Zusammenfassung - Kamp, Hermann (Heinrich IV)

"... von edler Herkunft und Lebensart". Adligsein im 10. und 11. Jahrhundert - Kamp, Hermann (Für Königtum und Himmelreich: 1000 Jahre Bischof Meinwerk von Paderborn)

Bilanzpolitisches Potential im Rahmen der Goodwillbilanzierung - Transaktionsgestaltung beim Unternehmenserwerb - Ebert, Michael; Simons, Dirk (KoR : Zeitschrift für internationale und kapitalmarktorientierte Rechnungslegung)

Pflegerobotik – Technikphilosophische Reflexionen und technikethische Empfehlungen - Weber, Jutta (Der Mensch als Vorbild, Partner und Patient von Robotern. Bionik an der Schnittstelle Maschine-Mensch)

Robotic Warfare, Human Rights & the Rhetorics of Ethical Machines - Weber, Jutta (Ethics and Robotics)

Inter- und Transdisziplinarität in den Technowissenschaften - Weber, Jutta; Allhutter, Doris (Newsletter des Österreichischen Instituts für Technikfolgenabschätzung)

A UML Frontend for IP-XACT-based IP Management - Schattkowsky, Tim; Xie, Tao; Müller, Wolfgang (Proceedings of DATE'09)
IP-XACT is a well accepted standard for the exchange of IP components at Electronic System and Register Transfer Level. Still, the creation and manipulation of these descriptions at the XML level can be time-consuming and error-prone. In this paper, we show that the UML can be consistently applied as an efficient and comprehensible frontend for IP-XACT-based IP description and integration. For this, we present an IP-XACT UML profile that enables UML-based descriptions covering the same information as a corresponding IP-XACT description. This enables the automated generation of IP-XACT component and design descriptions from respective UML models. In particular, it also allows the integration of existing IPs with UML. To illustrate our approach, we present an application example based on the IBM PowerPC Evaluation Kit.
Keywords: Unified modeling language; XML; Power system modeling; Application software; Master-slave; Power system management; Acceleration; Scattering; Software engineering; Software standards

Increased Accuracy through Noise Injection in Abstract RTOS Simulation - Zabel, Henning; Müller, Wolfgang (Proceedings of DATE'09)
Today, mobile and embedded real-time systems have to cope with the migration and allocation of multiple software tasks running on top of a real-time operating system (RTOS) residing on one or multiple system processors. Abstract RTOS simulations and timing analysis applies for fast and early estimation to configure it towards the individual needs of the application and environment. In this context, a high accuracy of the simulation compared to an instruction set simulation (ISS) is of key importance. In this paper, we investigate the accuracy of abstract RTOS simulation and compare it to ISS and the behavior of the physical system. We show that we can reach an increased accuracy of the simulation when we inject noise into the time model. Our results indicate that it is sufficient to inject uniformly distributed random time values to the RTOS real-time clock.
Keywords: Timing; Analytical models; Clocks; Performance analysis; Scheduling; Operating systems; Delay; Real time systems; Application software; Context modeling

Development of Automotive Communication Based Real-Time Systems - A Steer-by-Wire Case Study - Klobedanz, Kay; Kuznik, Christoph; Elfeky, Ahmed; Müller, Wolfgang (Proceedings of IESS09)
Safety-critical automotive systems must fulfill hard real-time constraints to guarantee their reliability and safety requirements. In the context of network-based electronics systems, high-level timing requirements have to be carefully mastered and traced throughout the whole development process. In this paper, we outline the management of scheduling-specific timing information by the application of a steer-by-wire design example. We apply the principles of the AUTOSAR-compliant Timing Augmented Description Language (TADL) following the methodology introduced by the TIMMO project[2]. Focus of the example will be the identification of end-to-end timing constraints and their refinement by means of stimuli-response event chains.
Keywords: Abstraction Level Controller Area Network High Abstraction Level Event Chain Automotive System

Integration abstrakter RTOS-Simulation in den Entwurf eingebetteter automobiler E/E-Systeme - Becker, Markus; Zabel, Henning; Müller, Wolfgang

Systematic Model-in-the-Loop Test of Embedded Control Systems - Krupp, Alexander; Müller, Wolfgang (Proceedings of IESS09)

Hardware-dependent Software for Multi- and Many-Core Embedded Systems - Doemer, R.; Gerstlauer, A.; Müller, Wolfgang (Proceedings of ASP-DAC'09)

Materielle Ressourcen – oder: Warum, wozu und wie haben und nutzen wir Güter? - Schlegel-Matthies, Kirsten; Methfessel, Barbara; Bigga, Regine (Haushalt & Bildung)

International corporate reporting: A comparative approach, by Clare Roberts, Pauline Weetman and Paul Gordon (fourth edition) - Kosi, Urska (The International Journal of Accounting)

ON THE LONG TIME BEHAVIOR OF FREE STOCHASTIC SCHRÖDINGER EVOLUTIONS - Bassi, Angelo; Dürr, Detlef; Kolb, Martin (Reviews in Mathematical Physics)
We discuss the time evolution of the wave function which is the solution of a stochastic Schrödinger equation describing the dynamics of a free quantum particle subject to spontaneous localizations in space. We prove global existence and uniqueness of solutions. We observe that there exist three time regimes: the collapse regime, the classical regime and the diffusive regime. Concerning the latter, we assert that the general solution converges almost surely to a diffusing Gaussian wave function having a finite spread both in position as well as in momentum. This paper corrects and completes earlier works on this issue.

The importance of catalyst oxidation for the growth of carbon nanotubes on Si substrates - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Mathys, Daniel (Carbon)

Lectura Dantis: Paradiso XXVI. - Steigerwald, Jörn (Deutsches Dante-Jahrbuch)

Photonic crystal fiber with a dual-frequency addressable liquid crystal: behavior in the visible wavelength range - Lorenz, A.; Kitzerow, Heinz-Siegfried; Schwuchow, A.; Kobelke, J.; Bartelt, H. (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Director Fields Around Spherical and Cylindrical Micro Particles in a Liquid Crystal Host - Matthias, H.; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

112Gb/s PolMux RZ-DQPSK with Fast Polarization Tracking Based on Interference Control - Wernz, H.; Bayer, S.; Olsson, B. E.; Camera, M.; Griesser, H.; Fuerst, C.; Koch, B.; Mirvoda, V.; Hidayat, A.; Noé, Reinhold (OFC: 2009 CONFERENCE ON OPTICAL FIBER COMMUNICATION, VOLS 1-5)

Unterhaltungsliteratur - Morrien, Rita (Metzler Lexikon DDR-Literatur. Autoren – Institutionen – Debatten)

Umwelt und Literatur - Morrien, Rita (Metzler Lexikon DDR-Literatur. Autoren – Institutionen – Debatten)

Julia Franck - Morrien, Rita (Metzler Lexikon DDR-Literatur. Autoren – Institutionen – Debatten)

Die ‚Lesbarkeit’ der (sozialistischen) Städte – Zur poetologischen Dimension der Architekturkontroversen in Brigitte Reimanns Romanfragment Franziska Linkerhand - Morrien, Rita (Literatur für Leser)

Multiplier-Free Real-Time Phase Tracking for Coherent QPSK Receivers - Hoffmann, Sebastian; Peveling, Ralf; Pfau, Timo; Adamczyk, Olaf; Eickhoff, Ralf; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

On Crack Analysis of Functionally Graded Materials with Material Forces - Mahnken, Rolf (IUTAM Symposium on Progress in the Theory and Numerics of Configurational Mechanics)

Deformation analysis for thermal shock using optical sensors and constitutive modelling - Sauerland, Kim-Henning; Mahnken, Rolf (Nondestructive Testing and Evaluation)

Mode Decomposition for Creep Simulation of Asymmetric Effects with Applications to Superalloys - Mahnken, Rolf (Key Engineering Materials)

Deformation and Damage Analysis of a Hybrid-Forming Tool under Thermal Shock Conditions - Mahnken, Rolf; Sauerland, K.-H.; Schneidt, A.; Gockel, F.-B. (PAMM)

Modellierung der Umwandlungsplastizität und Viskoplastizität niedrig legierter Stähle - Schneidt, Andreas; Mahnken, Rolf (PAMM)

Asymmetric effects of polymers in finite thermoviscoplasticity - Shaban, Ahmed; Mahnken, Rolf (PAMM)

Simulation of brittle crack growth in functionally graded materials - Mahnken, Rolf (PAMM)

Realization of Digital Coherent Receivers - Noé, Reinhold; Rueckert, Ulrich; Hoffmann, Sebastian; Pfau, Timo; Peveling, Ralf (2009 IEEE LEOS ANNUAL MEETING CONFERENCE PROCEEDINGS, VOLS 1AND 2)

Algorithms for Optical QAM Detection - Pfau, Timo; Noé, Reinhold (2009 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Multiplier-Free Realtime Phase Tracking in Digital Synchronous QPSK Receiver for Coherent Optical Detection - Hoffmann, S.; Herath, V.; El-Darawy, M.; Pfau, T.; Woerdehoff, C.; Peveling, R.; Rueckert, U.; Noé, Reinhold (2009 INTERNATIONAL CONFERENCE ON INDUSTRIAL AND INFORMATION SYSTEMS)

Towards Real-Time Implementation of Coherent Optical Communication - Pfau, T.; Peveling, R.; Herath, V.; Hoffmann, S.; Woerdehoff, C.; Adamczyk, O.; Porrmann, M.; Noé, Reinhold (OFC: 2009 CONFERENCE ON OPTICAL FIBER COMMUNICATION, VOLS 1-5)